PROTECTIVE ROLE OF LACTOBACILLUS ACIDOPHILUS AGAINST AFLATOXIN B1-INDUCED IMMUNOSUPPRESSION - M. K. Tipu; U. Saleem; T. Rehman; M. Aslam; K. Muhammad; K. Hussain; N. Bukhari; S. Hassan; Z. Hussain; M. Faisal; B. Ahmad (Journal of Animal and Plant Sciences, 2015)
Aflatoxin B1 is produced by Aspergillus flavus and Aspergillus parasiticus having hepatotoxic, mutagenic, carcinogenic and immunosuppressant properties. Current study was designed to investigate the effect of lactobacilli (as probiotic) on the immunosuppression in broilers with experimentally-induced aflatoxicosis and to compare outcomes with other established adsorbents. At 21st day of age, broilers were segregated into treatments: AFB (400 mg/kg feed); AFB+Probiotics (PBT2X: 2x109CFU); AFB+PBTX:109CFU; AFB+Mycosorb (1g/kg feed); Control (basal diet). Treatments were fed to the birds for 2 wk (week 4th and 5th of age). Data was collected during and for 2 wk post-exposure (Week 6thand 7th).AFB induced reduction of leukocyte count, relative weight of spleen and bursa of Fabricius and antibody titer against Newcastle Disease Virus. Lactobacilli significantly protected against suppressive effects of the toxin on TLC, lymphoid organs and antibody titers that was comparable with the mycosorb. It is concluded that lactobacilli significantly reduced the immunotoxicity of the toxin that might be due to decrease in absorption of the toxin.
Keywords: Aflatoxin; antibody titer; immunosuppression; lymphoid organs; probiotics